Exceptional Retreat of Kangerlussuaq Glacier, East Greenland, Between 2016 and 2018 - Brough, Stephen; Carr, J. Rachel; Ross, Neil; Lea, James M. (Frontiers in Earth Science, 2019)
Kangerdlugssuaq Glacier is one of Greenland’s largest tidewater outlet glaciers, accounting for approximately 5 % of all ice discharge from the Greenland ice sheet. In 2018 the Kangerdlussuaq ice front reached its most retreated position since observations began in 1932. We determine the relationship between retreat and: (i) ice velocity; and (ii) surface elevation change, to assess the impact of the retreat on the glacier trunk. Between 2016 and 2018 the glacier retreated ~5 km and brought the Kangerdlussuaq ice front into a major (~15 km long) overdeepening. Coincident with this retreat, the glacier thinned as a result of near-terminus acceleration in ice flow. The subglacial topography means that 2016-18 terminus recession is likely to trigger a series of feedbacks between retreat, thinning and glacier acceleration, leading to a rapid and high-magnitude increase in discharge and sea level rise contribution. Dynamic thinning may continue until the glacier reaches the upward sloping bed ~10 km inland of its current position. Incorporating these non-linear processes into prognostic models of the ice sheet to 2100 and beyond will be critical for accurate forecasting of the ice sheet’s contribution to sea level rise.